Perencanaan Pengembangan Alumni di Pondok Pesantren Modern (Studi di Pesantren Darul Muttaqien Bogor) - Dede Romdoni, Muhammad; Maemunah Sa'diyah (JPG: Jurnal Pendidikan Guru, 2024)
In every educational institution, human resources are the greatest strength of capital that has a major influence on the progress of the institution, therefore the development of alumni as human resources must be carried out with the aim of improving the quality of management of an institution. The method used in this research is a qualitative approach with data collection techniques, namely interviews with informants, field observations and documentation. The results of this research show that the planning stages for alumni development in modern Islamic boarding schools are: 1) Planning for alumni development is based on needs that have been determined according to criteria in the form of good academic results and potential skills possessed by alumni. 2) Alumni organization is determined by a foundation decree, has bylaws and long-term and short-term work programs. 3) Mobilizing alumni development through alumni tracking activities, conducting routine sharing sessions and giving awards to the best alumni in the form of undergraduate education scholarships which aim to continue the cadre program and 4) Supervision and management of alumni development is entirely under the supervision of the leadership and care of the pesantren with control in the TMI program (Tarbiyatul Muallimin Islamiyah).